Assessment of the Spine in a Healthy Working Population : A Radiographic Study of the Lumbrosacral Angle in Relation to Occupation in Southern Nigeria - Oyakhire, Michael Omon; Agi, Chukwu (Asian Journal of Medical Sciences, 2013)
Objective: This study was carried out to evaluate the effect of occupation on the Lumbosacral angle of the spine in a cohort of working adult Nigerians Method: Lateral radiographs from two hundred and twenty healthy working adults within the age range 18 to 55 years comprising 136 males (61.82%) and 83 females (38.18%), with a mean age=29.14(7.45) years were studied. Participants at the time of investigation were engaged in different physically demanding occupations with a minimum of one year job experience. The sample included a control group made up of undergraduate students from the University of Port Harcourt. Prior to data collection, all participants read and signed informed consent forms. Each lateral radiograph was evaluated using Fergusons sacral base-horizontal 2-line method. Statistical analysis was done using the computer based SPSS Version 17, Chicago IL, and a confidence level of 0.05 was accepted as indicative of statistical significance. Results: A statistically significant difference was found between the four groups in terms of age, gender and occupation. The lumbosacral angle of the groups engaged in physically demanding occupations were significantly higher than the control (undergraduate students). Conclusion: The lumbar curves are designed to increase the resilience of the vertebral column. Over a time period, physically demanding jobs are likely to cause various degrees of significant alterations in the lumbosacral configuration DOI: http://dx.doi.org/10.3126/ajms.v5i2.8888 Asian Journal of Medical Science, Volume-5(2) 2014: 99-105